SERVICE OVERTIME DAN KAROSHI : KONSEKUENSI DARI ETOS KERJA JEPANG - Arsi Widiandari (Universitas Diponegoro, 2015)
After defeated on World War II, Japan economy has recover and become one of developed country in Asia. One of the factor that give contribute to Japanese economy rising is Japanese spirit. Company usually teached work culture to every worker that can be seen from Japanese work ethic. For example ideology of Family Methaphore, Shushin Koyo seido (Lifetime employment) Nenko Joretsu ( Salary based on seniority ) and Kigyou betsu Kumiai (Union based on corporation). The work culture practice in Japan company has had positive and negative consequences. As we know, that it has great contributed to Japanese economy development it self. But, it also bring a number of social problem especially to many workers. Service overtime and Karoshi are the example of the consequences of Japan work ethic practice until nowadays. Worker are expected to give their deducation and loyality to job company. This paper will try to give explanation about the consequences of Japan work ethic practice in Japan.